ISTI‘ĀRAH DALAM AL-QUR’AN SURAH AL-FAJR: TELAAH TAFSIR ALI ASH-SHABUNI - Nurul Aulia Ersa Putri; Arifinsyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article aims to analyze the forms of isti‘ārah found in Surah Al-Fajr and examine their interpretation based on Ali Ash-Shabuni’s Shafwatut Tafasir. In the book Shafwatut Tafasir, Ali Ash-Shabuni pays special attention to linguistic aspects (balaghah) to reveal the beauty and depth of the meaning of the Al-Qur'an. In examining the isti'arah in surah Al-Fajr Ali Ash-A-Shabuni tends to use the At-Taisir style, namely explaining complex balaghah terms in language that is easy to understand. This study employs a qualitative method with a library research approach. Primary data are derived from the Qur’an, specifically Surah Al-Fajr, and Ali Ash-Shabuni’s tafsir, while secondary data consist of books on balaghah, Qur’anic sciences, and relevant scholarly journal articles. Data collection techniques include documentation and content analysis. The findings indicate that Surah Al-Fajr contains various forms of isti‘ārah, both tashrihiyyah and makniyyah, which function to affirm Allah’s omnipotence, depict human psychological states, and reinforce moral and eschatological messages. As in the word Al-Fajr Ali Ash-Shabuni suggests that the word dawn is a symbol of the emergence of the light of Islam after the darkness of polytheism. Ali Ash-Shabuni’s interpretation highlights linguistic and contextual dimensions, enabling a comprehensive understanding of the metaphorical meanings embedded in Surah Al-Fajr.